2018
DOI: 10.1037/cfp0000107
|View full text |Cite
|
Sign up to set email alerts
|

Emotionally focused therapy and eye movement desensitization and reprocessing: An integrated treatment to heal the trauma of infidelity.

Abstract: Despite the prevalence of infidelity and the serious harm it causes relationships, scarce clinical literature exists about how to use trauma-informed approaches to help couples in conjoint therapy. Emotionally focused therapy (EFT) and eye movement desensitization and reprocessing (EMDR) have been empirically proven in their own right to be effective in the treatment of trauma and couples, respectively, and were utilized conjointly in this article as a means to heal trauma related to infidelity in couple thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Another effect is evidenced in the investigation conducted by Negash, Carlson, and Linder (2018), that pays attention to psychological therapy which helps patients to identify conflicts in their relationships that have not been tackled before [ 21 ]. This identification was very useful for them to start a conflict resolution process that improves their relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another effect is evidenced in the investigation conducted by Negash, Carlson, and Linder (2018), that pays attention to psychological therapy which helps patients to identify conflicts in their relationships that have not been tackled before [ 21 ]. This identification was very useful for them to start a conflict resolution process that improves their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Another research that explores the impact of a similar therapy is conducted by Negash, Carlson, and Linder [ 21 ]. They evaluated the effects of the combination of two psychological therapies: Emotionally focused therapy (EFT) and Eye movement desensitization and reprocessing (EMDR), which were employed to treat the trauma suffered by couples who have experienced infidelity.…”
Section: Introductionmentioning
confidence: 99%
“…Many models exist for treating infidelity (e.g., Atkins et al, 2005; DiBlasio, 2000; Fife et al, 2008; Gordon et al, 2004; Halford & Markman, 1997; Johnson, 2005; Lusterman, 1998; Negash et al, 2018; Spring, 1996), but very few have more than practice‐based evidence or single case studies to support their use. A good review of practice‐based evidence can be found in Dupree et al (2007).…”
Section: Empirically Supported Treatments For Infidelitymentioning
confidence: 99%
“…Beginning with the discovery of the infidelity, there is growing evidence that the healing work begins with the betrayed individual being assessed for trauma (Duba Sauerhaber & Disque, 2016; Leone, 2013; Negash et al, 2018). Leone (2013) stated that counselors should expect emotional reactivity and help the betrayed client manage the affective flooding that occurs from trauma, grief, and loss of attachment as the first crucial step to healing.…”
Section: Treatment Researchmentioning
confidence: 99%
“…Leone (2013) stated that counselors should expect emotional reactivity and help the betrayed client manage the affective flooding that occurs from trauma, grief, and loss of attachment as the first crucial step to healing. Approaches to addressing these responses and rebuilding attachment and trust include psychoeducation (Dean, 2011), eye movement desensitization and reprocessing, and emotionally focused therapy (Negash et al, 2018). Duba Sauerhaber and Disque (2016) emphasized that healing begins with rebuilding trust.…”
Section: Treatment Researchmentioning
confidence: 99%